The Effect of Using Discovery Learning Model in High School Physics Learning: A Meta-Analysis (Jurnal Pendidikan Fisika, 2022)
Discovery learning is one of the learning models recommended by the 2013 Indonesian curriculum to meet the demands of 21st-century learning. The purpose of this study is to determine the effect of the discovery learning model based on class level, learning materials, student learning competencies, and learning media used. This type of research is a meta-analysis by calculating the value of effect size (ES). The data collection technique in this study is using documentation techniques. The analytical techniques used are quantitative analysis for value and qualitative analysis to analyze research data. The study used 26 articles consisting of 21 national articles and 5 international articles. The results of this study indicate that, first, the discovery learning model is more effectively applied to class X with an ES of 1.38, which is in the high category. Second, the discovery learning model is more effectively applied to measurement material with an ES of 3.24, which is in the high category. Third, the discovery learning model is more effective for increasing learning competence in the form of mastery of concepts and critical thinking skills of students with an ES of 1.70, which is in the high category. Finally, the tracker software media is more effective in learning physics with ES 2.32, which is in the high category. Overall, it can be concluded that the discovery learning model has a positive effect on physics learning.